Demand evaluating the nexus: factors propelling Malaysia’s export competitiveness in natural rubber downstream products/ Farah Hanani... [et al.] - -, Farah Hanani; Othman, Norashida; Wahab, Siti Norida; Oktarina, Sachnaz Desta (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
Malaysia, although being a significant player in the international rubber market, faces difficulties in properly capitalising on rubber exports to strengthen its national accounts. This can be attributed to the challenges posed by limited land availability and uneven productivity distribution. Hence, the aims of this study were: (i) to evaluate Malaysia's comparative advantage in the production of natural rubber downstream products compared with Thailand, the primary natural rubber producer and (ii) to examine the influence of trade openness (TO), foreign direct investment (FDI), gross domestic product (GDP), and inflation (INF) on Malaysia's export competitiveness in the natural rubber industry. This study utilised secondary data from the United Nations Commodity Trade Statistics Database (COMTRADE) and World Bank data spanning 32 years, from 1990 to 2021. The study used regression analysis and the autoregressive distributed lag (ARDL) technique to uncover the index of relative export advantage (RXA). The RXA index revealed that Thailand was more competitive in natural rubber exports than Malaysia. Furthermore, the ARDL technique findings indicated that trade openness (TO) and inflation (INF) had a considerable statistical impact on Malaysia's export competitiveness in the natural rubber industry. Meanwhile, foreign direct investment (FDI) significantly affected export competitiveness in the long term.